Effect of Palm Oil Emulsion Waxing on the Storage of Some Fruits - จูฑะมงคล, รุ่งทิพย์; ศรีม่วง, จันจิรา; สุขสุวรรณ, จิตติมา (KKU Science Journal, 2012)
Limes and mangoes were coated with three wax emulsions, namely palm stearin (PS) carnauba wax (CW) alone and palm stearin mixed with carnauba (CR). Those emulsions were prepared as labolatory and four levels of emulsion concentration were studied. After waxing, samples were both physically and chemically examined. The optimum stability formular of PW consitiator121 grams of palm wax, 42 of oleic acid, 28 of triethanolamine,56 of water and 48 of paraffin wax formular. The quantity of wax emulsion used varied depending on the formulation. Limes coated with CW gave the highest weight loss (3.25-5.45%). All emulsions used were found to retain of chlorophyll color and weight loss can be reduced. Dipping limes with 10% CW had 13.9% weight loss after 16 days storage at 29-32 ºC, while the unwaxed one had 30.6% weight loss. Mangoes waxed with 6% PS had 4.57% weight loss whereas unwaxed samples had 15.76% weight loss after 11 days storage at 29-32 ºC. Respiration rate and juice content were decreased by waxing.